Queering boundaries: visual Activism and representations of sexuality in the work of contemporary South African artists - Littleford, Lara (Rhodes University, Faculty of Humanities, Department of Fine Art, 2017)
Zanele Muholi, a photographer and visual activist, and Sabelo Mlangeni, a photographer, explore the different ways of representing gender, particularly transgenderism, and sexuality, particularly homosexuality, in their photography. Muholi and Mlangeni document the daily lives and lived realities of people who are black and gay, lesbian, bisexual and transgender (LGBT) in South Africa. African sexuality remains a contested subject that is difficult to discuss in light of the controversies it provokes due to colonial attitudes toward African bodies. In this instance, colonial attitudes toward African sexuality have exoticised African bodies. Moreover, hyper-sexuality is ascribed to bodies that are black and male, whilst fetishising and objectifying black female bodies. Furthermore, representations of homoeroticism in Africa transgress and challenge dominant ideologies of sexuality and gender in an African context. In this sense, Muholi and Mlangeni directly address tension and resistance between individual and community. Such tensions are found within and between categories of African-ness, whereby homosexuality and transgenderism are regarded as being 'un-African' and an import from the West. For example, Muholi represents the existence of homosexuality and transgenderism in her photography in order to subvert the notion that homosexuality is 'un-African', attempting to complicate the conceptions of identity, gender and sexuality in South Africa. Muholi's photography is used as a vehicle for her 'visual activism', which purports to create socio-political awareness surrounding homophobia, transgenderism, and epistemic injustice in South Africa. The visual imagery of these two artists investigates the boundaries that are set by various social, political and cultural constructs. These boundaries inform existing social, political and cultural attitudes toward homosexuality and transgenderism, and these homophobic and transphobic attitudes result in crimes committed against homosexual and transgender individuals, such as hate crimes, which includes 'curative/corrective' rape, the prevalence of which is rising at an alarming rate. Muholi's photography and visual activism seek to create visibility in order to raise public awareness of hate crimes, victimisation, alienation and stigmatisation that homosexual and transgender South Africans, specifically those individuals living in township areas, face on a daily basis. These two artists represent sexuality as a site of contestation and, as such, heteronormative traditions, hegemonic social structures, and cultural conventions are transgressed and contested in their photography.
Keywords: Homosexuality in art -- South Africa; Photographers, Black -- South Africa; Gay photographers -- South Africa; Lesbian photographers -- South Africa; Transgender people in art -- South Africa; Muholi, Zanele; Mlangeni, Sabelo